THE INFLUENCE OF TEACHING SKILLS ON STUDENTS’ LEARNING INTEREST - Lika, Agnes Desna; Samsinar, Samsinar; Rijal, Abdul; Nuraisyiah, Nuraisyiah; Tikollah, M Ridwan (Universitas Labuhanbatu, 2024)
Thisl study aimsl to determinel thel effect ofl the lteacher's teachingl skills on the learningl interest of classl XI students ofl the accountingl expertise programl at SMK Negeri 1l Makassar. The variablesl in thisl study arel the lteacher's teaching skillsl (X) andl students' interest in learning (lY). This typel of researchl is quantitativel research. Thel population inl this studyl were classl XIl AKL 1l and XI AKLl 2 SMK Negeril 1 Makassar consistingl of 71 lstudents. The samplingl technique usesl a saturatedl sample. Datal collection techniquesl using questionnairesl and ldocumentation. Thel data analysisl technique is descriptivel percentage lanalysis, instrument testl consisting ofl validity andl reliability ltests, and hypothesisl testing consistingl of simplel linear regressionl lanalysis, t-testl and coefficientl ofl ldetermination. Based onl thel resultsl of thel descriptive lanalysis, the lteacher's teaching skills obtainedl an averagel actual scorel of 78.66 percentl which wasl included inl the high categoryl while students' learningl interest obtained anl average actuall score ofl 74.85 percent whichl was includedl in thel high category. Thel results ofl the datal analysis obtainedl a simplel linear regressionl equation modell Y = 29.800 + 0.178X, whichl means thatl for eachl addition ofl one valuel of thel teacher's communicationl ability, thel value ofl student learningl satisfaction increases byl 0.178. Froml the analysis ofl the coefficientl of determinationl (r2) a value of l7.6 percent is obtained. This means that the teacher's communication skills contribute tol student learningl satisfaction by 7.6 percentl and the remaining 92.4 percentl is influenced byl other lfactors. And from the lt-test results obtainedl a significantl value ofl 0.02 <l 0.05, whichl means thatl there isl al significant influencel between thel teacher's communication skillsl and lstudent learning satisfaction, thusl the hypothesisl is accepted.